بەکارهێنانی بنەماکانی گرافیک دیزاین لە پێگەی ئەلکترۆنی زانکۆ حکومییەکانی هەرێمی کوردستان توێژینەوەیەکی شیکارییە لەسەر پێگەی ئەلکترۆنی زانکۆی سلێمانی و زانکۆی ڕاپەڕین - عەلی, م.ی.شۆخان ئەبوبەکر (Sulaimani Journal for Humanities, 2023)
Graphic design is a visual communication tool. The purpose of graphic design work is to find appropriate ways of presenting message content to reach the user. Numerous methods are used to create and combine symbols, images and words to construct messages and ideas. All design elements emphasize the content of the message. One of the main functions of public relations is the communication activity that conveys the organization's message to the community. An organization's success depends on its ability to communicate with the public and generate a positive mental image and a good reputation. Websites are one of the most effective new tools for reaching the largest audience. The main problem arises from the question of to what extent institutions (University of Sulaimani and University of Raparin) have used and adhered to graphic design principles on their websites and to what extent they adhere to those principles? To what extent has adherence to these principles contributed to the institution's objectives? To achieve the objectives of this study, the descriptive method and survey were used. The content analysis method is relied on to conduct this study. The research community consists of two public universities: (University of Sulaimani and University of Raparin). The study sample is a randomly drown sample from both universities. The time limit for receiving articles from the websites is form (January 1, 2022) to (Jun 1, 2022). The main conclusions reached by the researcher are: The principle of equal balance was largely observed at both universities. The contrast principle was observed and a contrast in size and arrangement were the most common. The hierarchy principle was observed and repeating hierarchies was used in designing the pages of websites in a consistent manner. Repetition principle was followed, repeating colors and images were most commonly used at both universities. Following the alignment principle, horizontal and two-sided alignment are more commonly used. Both universities valued and nurture the principle of image value in all subjects. Following the principle of emphasis, the principle of contradiction is one of the main principles that has been used. In designing the websites of both universities, colors were used appropriately according to 2 or 3 colors and color scales. Neither universities uses backgrounds, which makes it difficult for users to read. University of Sulaimani used many images in news and announcements, while University of Raparin only used one image or the logo of the institution for each article. Both universities publish information about their institutions and activities on their websites. Both universities publish information about their institutions and activities on their websites. Regarding communication, both universities have emails, phone numbers and Facebook pages. University of Raparin has the most news and information, all academic discussions on masters and doctoral degrees, publications of teacher’s research in international journals, book publication, national events, conferences and seminars and intercollegiate sports activities have been published.
Keywords: Keywords Principles; Graphic Design; Websites